Fracture behavior of AZ31B magnesium alloy under high-temperature ultrasonic-assisted shearing with related ductile-brittle transformation mechanism - Yue Meng; Lifeng Ma; Weitao Jia; Zhiquan Huang; Hongbo Xie; Fangkun Ning; Junyi Lei (Journal of Materials Research and Technology, 2024)
A wide width is one of the fundamental requirements for magnesium alloy sheets to fulfill the lightweight needs of the aerospace and rail transportation industries. Nevertheless, ensuring the dimensional integrity of wide-format magnesium alloy sheets is a challenge in most manufacturing facilities. Simultaneously, processing operations are susceptible to encountering production issues, including but not limited to significant loss of raw materials, elevated costs, environmental contamination, and safety risks. Therefore, to fulfill the operational demands of the hot rolling finishing line for wide sheets made of magnesium alloy, the present study employed ultrasonic-assisted shearing (UAS) to carry out a high-temperature shearing test investigation on the AZ31B magnesium alloy sheet. In this research, we employed scanning electron microscopy, optical microscopy, and a micro-hardness tester to investigate the relationship between ultrasonic amplitude and fracture behavior, deformation mechanism, and mechanical properties of magnesium alloy sheets following exposure to ultrasonic vibration. The fracture morphology of the sheet fracture demonstrates that the behavior of the magnesium alloy sheet fractures under ultrasonic vibration changes from ductile fracture under conventional shearing to brittle fracture under ultrasonic-assisted shearing. The primary cause of this transformation between ductile and brittle is the effect of ultrasonic vibration on the material's internal energy. High-energy ultrasonic amplitude action causes magnesium to absorb a significant amount of ultrasonic energy. This results in an increase in the number of dynamic re-crystallization grains in the material organization, a decrease in the number of twins, and significant refinement of the grains. The sheet's hardness also changes along the rolling and normal directions, with a uniform distribution. The magnesium alloy sheet's fracture quality is optimal when the ultrasonic amplitude is 10 μm in the UAS process. This treatment results in notable enhancements in the section's straightness and brightness. Our study aims to advance the mass manufacturing of wide-format magnesium alloy sheets by investigating a cost-effective and high-yield technique for shearing magnesium alloy sheets.